2016
DOI: 10.1021/acssuschemeng.6b01677
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytic Transfer Hydrogenation of Ethyl Levulinate to γ-Valerolactone over a Robust Cu–Ni Bimetallic Catalyst

Abstract: An efficient and robust bimetallic catalyst has been developed for the transfer hydrogenation of biomass derived ethyl levulinate to γ-valerolactone with 2-butanol as the hydrogen donor. Several bimetallic catalysts were prepared and characterized by Brunauer−Emmett−Teller, transmission electron microscopy, X-ray power diffraction and X-ray photoelectron spectrometry. They exhibited different catalytic activities in the catalytic transfer hydrogenation (CTH) reaction. Results showed that 10Cu-5Ni/Al 2 O 3 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 67 publications
4
66
0
Order By: Relevance
“…In general hydrogenation catalysis studies have either relied on the traditional precious metals or applied the same impregnation/deposition methods used to form metal nanoparticles for those catalysts to the synthesis of materials with copper as the active component. For example, Cu-Ni/Al 2 O 3 , with Ni the minor component, prepared by incipient impregnation has been reported [18] and showed 50% GVL yield after 2 h of reaction at 150 °C for the catalytic transfer hydrogenation of ethyl levulinate.…”
Section: Introductionmentioning
confidence: 99%
“…In general hydrogenation catalysis studies have either relied on the traditional precious metals or applied the same impregnation/deposition methods used to form metal nanoparticles for those catalysts to the synthesis of materials with copper as the active component. For example, Cu-Ni/Al 2 O 3 , with Ni the minor component, prepared by incipient impregnation has been reported [18] and showed 50% GVL yield after 2 h of reaction at 150 °C for the catalytic transfer hydrogenation of ethyl levulinate.…”
Section: Introductionmentioning
confidence: 99%
“…In the control experiment, single metal catalysts of Ni and Cu could be recycled only for two times, because of accumulation of carbonaceous species on the catalyst surface which blocked active sites and detached metals from the supports. On the contrary, the bimetallic catalyst attained modulated electron properties by alloying ,. When Cu−Ni/CeO 2 and Cu−Ni/ZrO 2 catalysts was tested up to 6 th runs (Figure c), the conversion and 2‐methoxy‐4‐methylphenol selectivity were dropped from 78.3 to 60.5% and from 85.6 to 75.3% after 6 th runs, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…However, the results of the catalyst with different Ni/Cu ratio shows that both the yield of bio‐oil and the conversion of lignin decreased with the increase of Cu content in the Ni−Cu/AC. Many studies on bimetallic catalyst have found that the synergistic effect of the two metals would increase the active site on metal catalyst, reduce the size of the metal particle, and improve the dispersion of the metal, which in turn increase the catalytic activity of the bimetallic catalyst . It has also been reported that the presence of Cu could lower the reduction temperature of Ni species and provided more reduced Ni sites for the hydrogenation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Toledano et al used Ni/Al‐SBA‐15 catalyst to depolymerize lignin, and 30% yield of bio‐oil with the products distribution of phenols, aromatic aldehydes, ketones and esters was achieved. According to our previous reports, the Ni−Cu bimetallic catalyst has high catalytic activity in the synthesis of ethyl levulinate to γ‐amyl ester. The metal Cu in catalyst is easy to lose the peripheral electrons during the hydrogenation reaction, resulting in a decrease in catalytic activity.…”
Section: Introductionmentioning
confidence: 87%